ASSESSMENT OF SEASONAL VARIATIONS OF WATER QUALITY PARAMETERS OF SAVITRI RESERVOIR, POLADPUR, RAIGAD DISTRICT, MAHARASHTRA - LIANTHUAMLUAIA,; ASHA T. LANDGE,; C. S. PURUSHOTHAMAN,; DESHMUKHE , GEETANJALI; K. RAMTEKE, KARANKUMAR (The Bioscan, 2013)
The present study assessed the seasonal variations of the selected water quality parameters of Savitri reservoir from February, 2012 to January, 2013. The range of the selected water quality parameters were observed to have a seasonal significant difference for temperature (24-33.66ºC), alkalinity (34-76.66 mg/L), hardness (36.67-62.67 mg/L), dissolved oxygen (6.4-9.47 mg/L), carbon dioxide (0-8.93 mg/L), phosphate (0.011-0.04 mg/L), ammonia (0.026-0.182 mg/L), nitrate (0.058-0.315 mg/L) and silicate (8.59-23.06 mg/L), whereas no significant seasonal variations were observed on pH (7.3-7.8), chloride (5.57-10.3 mg/L) and nitrite (0.006-0.093 mg/L). Temperature, dissolved oxygen, alkalinity, hardness, chloride and phosphate were observed to be maximum in summer; pH, nitrite and nitrate in monsoon; carbon dioxide, ammonia and silicate in winter. Factor analysis showed that most of the selected water quality parameters except chloride are significant to water quality variations in all seasons. The present study clearly evidenced that Savitri reservoir is suitable for fisheries, irrigation and drinking purposes.